EXISTENCETOURISM DESTINATION DEVELOPMENT PURA AGUNG BLAMBANGAN ASSESSED OFOFFROM HISTORICAL VALUE IN TEMBOKREJO VILLAGE, MUNCAR DISTRICT, BANYUWANGI DISTRICT - Risa Nurhidayah Novera; Tofan Priananda Adinata; dhalia soetopo (International Jurnal of Education Schoolars, 2020)
Pura Agung Blambangan is a temple that has historical links to the last Hindu kingdom, namely the Blambangan Kingdom. Pura Agung Blambangan is very often visited by Hindus from the Banyuwangi Regency area to outside the Banyuwangi area. This temple is included in the Kahyangan Jagat temple, and uses the Tri Mandala concept which consists of Nista Mandala, Madya Mandala, and Utama Mandala. Pura Agung Blambangan apart from being a place of worship is also used as religious tourism, especially for Hindus. The development of Pura Agung Blambangan can be seen in terms of the building which is progressing and the facilities inside the temple are adequate as a place for tourism or religious tourism. The existence of the temple can have impacts, especially for residents around Pura Agung Blambangan, namely from the economic level. The author tries to research by referring to the formulation of the problem, including: 1) How is the history of the establishment of Pura Agung Blambangan in Tembokrejo Village, Muncar District, Banyuwangi Regency. 2) How is the development of Pura Agung Blambangan tourism destination in terms of historical value. 3) How is the existence of the development of the tourism destination of Pura Agung Blambangan, Tembokrejo Village, Muncar District, Banyuwangi Regency. The method used in this research is descriptive qualitative research method with the main sources consisting of traditional stakeholders, temple managers, tourists, and temple pengemong. While data collection is obtained from observations, interviews, and documentation. The data analysis stages are the stage of data collection, data education, data presentation, and drawing conclusions. From the results of the research, the researcher concludes that Pura Agung Blambangan has experienced development as a religious tourism place which is always visited by tourists, the majority of whom come from Bali. Pura Agung Blambangan also has historical value, which is seen from the umpak songo site which is a legacy of the Blambangan Kingdom.